A High Precision Star Image Pre-Processing Method Against Earth-Atmosphere Radiation of Star Sensor - Liu Yuxin, Wang Xinlong, Hu Xiaodong, Wang Xun (Hangkong bingqi, 2023)
Star sensors installed on near-space vehicles are susceptible to earth-atmosphere radiation. As a result, the accuracy of star extraction and the performance of celestial system is significantly degraded. Aiming at this problem, a high precision star image pre-processing method to eliminate earth-atmosphere radiation is proposed. By analyzing the propagation mechanism of earth-atmosphere radiation, the atmospheric scattering model and ground reflection model are established, and an accurate earth-atmosphere radiation intensity model is constructed. Subsequently, the radiation intensity model is transformed into the background grayscale model in local ranges with the analysis of the relationship between the transmission path of the earth-atmosphere radiation received in the local ranges of the star sensor image plane and the pixel coordinates. Furthermore, the background estimation method is used to accurately estimate and compensate the stray light background under the influence of the earth-atmosphere radiation. Eventually, the performance of the proposed method is verified by simulated and real star images. The results show that the proposed method can effectively improve the SNR of star images and the accuracy of star extraction, and has good anti-interference performance.